A novel research on isolation and characterization of Photobacterium damselae subsp. damselae from Pacific white shrimp, Penaeus vannamei, displaying black gill disease cultured in China. Issue 5 (20th March 2020) - Wang, Ziyan; Shi, Chengyin; Wang, Hailiang; Wan, Xiaoyuan; Zhang, Qingli; Song, Xiaoling; Li, Ge; Gong, Miao; Ye, Shigen; Xie, Guosi; Huang, Jie
Abstract: In June 2019, massive mortalities of cultured Penaeus vannamei occurred in a local farm in Hainan Province, China. The diseased shrimp displayed evident black gills. Three bacterial strains 20190611001, 20190611007 and 20190611022 were isolated from hepatopancreas and gills of the diseased shrimp and identified as Photobacterium damselae subsp. damselae based on the sequence analysis of 16S rRNA and toxR genes. These three isolates showed haemolytic activities. Of them, strain 20190611022 isolated from hepatopancreas was selected and processed for pathogenic analysis. The calculated median lethal dose (LD50 ) was 9.75 ± 4.29 × 10 5 CFU/g (body weight) by challenging P. vannamei via reverse gavage. The diseased shrimp displayed enlarged hepatopancreatic tubules and sloughing of epithelial cells in tubular lumens. The strain 20190611022 was also characterized by the testing of API 20NE systems and antibiotic susceptibility. The results of disc diffusion test showed that strain 20190611022 was sensitive to chloramphenicol, compound sulfamethoxazole, cefoperazone, ceftriaxone, ceftazidime and cefuroxime. To our knowledge, this is the first report of isolation and characterization of Photobacterium damselae subsp. damselae from natural diseased P. vannamei . Our findings can serve as a basis for further studies of its pathogenicity and provide technological support for disease controlling in shrimp aquaculture.